Bio sorption of hexavalent chromium using biomass of microalgae scenedesmus SP - Pradhan, Debabrata; Devi, Niharbala; Behari Sukla, Lala (International Journal of Engineering and Technology, 2018)
Hexavalent chromium (Cr (VI)) is a toxic metal ion present in the water environment. The water samples collected from different points of the seepages of Sukinda Chromite mines are of Odisha, India were found to be high content of Cr (VI). Therefore, its biosorption onto the biomass of microalgae Scenedesmus sp. was examined in this study. The biomass of microalgae was generated using a raceway pond specially designed for their growth. Different biosorption parameters, such as initial pH, contact time, initial Cr (VI) concentration, biosorbent dosage, particle size distribution of the microalgae biomass and temperature, were found to affect the Cr (VI) loading onto the biomass. The maximum biosorption efficiency of Cr (VI) was found to be 93.1% at an optimum condition of contact time, 120min; Cr (VI), 10mg.L-1; solid-liquid ratio, 10%(w/v); pH, 1.0; temperature, 30oC; particle size, -75+45Î¼m; stirring, 300rpm. The presence of different functional groups, such as amides, acids, aldehydes, and halides, confirmed by the FTIR analysis technique were the reason for the high uptake of metals.Â Â Â